Analisis Tingkat Pengetahuan dan Partisipasi Masyarakat dalam Pencegahan dan Pengendalian Kebakaran Lahan Gambut di Taman Hutan Raya Orang Kayo Hitam (Studi Kasus: Desa Seponjen dan Desa Sungai Aur, Kecamatan Kumpeh, Kabupaten Muaro Jambi, Provinsi Jambi) - Windra Setiawan Pohan; Hutwan Syarifuddin; Hamzah Hamzah (Universitas Batanghari Jambi, 2023)
This study aims to analyze the level of community participation and the relationship of between community knowledge with participation in the fire prevention and suppression from peat in Orang Kayo Hitam Grand Forest Parks (TAHURA), Jambi Province. Research uses a mixed method by combining quantitative and qualitative research. The qualitative data sampling uses purposive sampling by collecting data through in-depth interviews. The analytical method used is quantitative descriptive analysis method supported by qualitative and cross tabulation methods. For the analysis of the association relationship using the Spearman Rank correlation formula method with respondents (n)>30. To analyze the comparison of the level of knowledge and community participation, the t-test was performed using the independent t-test. Based on data analysis, it is known that the level of participation for the community of Seponjen Village is at the level of Partnership, while the level of participation of Sungai Aur villagers is at the level of manipulation. The level of knowledge and level of community participation in Seponjen Village is higher than the knowledge of the Sungai Aur Village community. The relationship of knowledge to community participation in Seponjen and Sungai Aur Villages has a strong enough correlation coefficient, rs seponjen = 0,481 and rs sungaiaur = 0,290. Correlation value rs (Spearman Rank correlation coefficient) shows that there is a very significant effect (Î± = 0.01) between knowledge of the level of community participation in the prevention and control of peatland fires in Orang Kayo Hitam Grand Forest Parks (TAHURA). The strategy to increase and strengthen knowledge and community participation in both villages can be done through assistance to increase knowledge through socialization and community participation through training and improvement of supporting facilities and technical knowledge on the use of various facilities needed in the form of community empowerment to increase knowledge and participation in prevention and control fire peat fires in Orang Kayo Hitam Grand Forest Parks (TAHURA).